Are Telecommuters Remotely Good Citizens? Unpacking Telecommuting's Effects on Performance Via I‐Deals and Job Resources. Issue 2 (15th August 2014) - Gajendran, Ravi S.; Harrison, David A.; Delaney‐Klinger, Kelly
<x xml:space="preserve">Abstract</x> Despite their widespread adoption, concerns remain that virtual work arrangements can harm employee job performance and citizenship behavior. Does telecommuting really hamper these critical dimensions of employee effectiveness? To answer this question, we develop a theoretical framework linking telecommuting to task and contextual performance via a dual set of mechanisms—reflecting proposed effects of i‐deals and job resources. Further, we propose that the meaning of and outcomes from these paths depend on the social context surrounding telecommuting. We test the framework with field data from 323 employees and 143 matched supervisors across a variety of organizations. As predicted, we find that telecommuting is positively associated with task and contextual performance, directly and indirectly via perceived autonomy. These beneficial effects are contingent upon two aspects of the social context: leader‐member exchange and signals of its normative appropriateness among coworkers and one's supervisor.